Altering the Proteoglycan State of Transforming Growth Factor β Type III Receptor (TβRIII)/Betaglycan Modulates Canonical Wnt/β-Catenin Signaling - Jenkins, Laura M. (J Biol Chem, 2016)
Hyperactive Wnt/β-catenin signaling is linked to cancer progression and developmental abnormalities, making identification of mechanisms controlling Wnt/β-catenin signaling vital. Transforming growth factor β type III receptor (TβRIII/betaglycan) is a transmembrane proteoglycan co-receptor that exists with or without heparan and/or chondroitin sulfate glycosaminoglycan (GAG) modifications in cells and has established roles in development and cancer. Our studies here demonstrate that TβRIII, independent of its TGFβ co-receptor function, regulates canonical Wnt3a signaling by controlling Wnt3a availability through its sulfated GAG chains. Our findings revealed, for the first time, opposing functions for the different GAG modifications on TβRIII suggesting that Wnt interactions with the TβRIII heparan sulfate chains result in inhibition of Wnt signaling, likely via Wnt sequestration, whereas the chondroitin sulfate GAG chains on TβRIII promote Wnt3a signaling. These studies identify a novel, dual role for TβRIII/betaglycan and define a key requirement for the balance between chondroitin sulfate and heparan sulfate chains in dictating ligand responses with implications for both development and cancer.